Pelatihan Instalasi dan Implementasi Perangkat Closed Circuit Television (CCTV) di Perumahan Asri Pratama RT. 009 RW 009 Desa Sukadami Kecamatan Cikarang Selatan Kab. Bekasi Jawa Barat - Tumini; Agmawarnida; Endra Saputra (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This community service activity aims to enhance neighborhood security through training on the installation and implementation of CCTV systems at Perumahan Asri Pratama, Cikarang Selatan, Bekasi. The program was carried out as a form of support for residents’ efforts to create a safer and more comfortable environment. The implementation methods included initial coordination with community leaders and residents, the delivery of theoretical materials on the basic concepts of surveillance systems, and hands-on practice in installing CCTV devices. Participants were guided to understand the installation flow, device configuration, and monitoring procedures. Evaluation results indicate that 85% of participants were able to comprehend the concepts of CCTV installation and operation. In addition, three CCTV units were successfully installed at strategically selected points within the neighborhood. This activity demonstrates that the utilization of simple surveillance technology can serve as an effective and applicable solution for improving residential security. The program is expected to be sustainable through continuous community-based management.